MiR-204-3p Inhibited the Proliferation of Bladder Cancer Cells via Modulating Lactate Dehydrogenase-Mediated Glycolysis - Guo, Jinan; Zhao, Pan; Liu, Zengqin; Li, Zaishang; Yuan, Yeqing; Zhang, Xueqi; Yu, Zhou; Fang, Jiequn; Xiao, Kefeng (Frontiers in Oncology, 2019)
MicroRNAs (miRNAs) are endogenous non-coding RNAs that negatively regulate the expression of downstream targeted mRNAs. Increasing evidence has suggested that miRNAs act as tumor suppressors or oncogenes to interfere the progression of cancers. Here, we showed that miR-204-3p was decreased in bladder cancer tissues and cell lines. Down-regulation of miR-204-3p was significantly associated with poor prognosis in bladder cancer patients. Overexpression of miR-204-3p inhibited proliferation and induced apoptosis in bladder cancer cells. Furthermore, miR-204-3p was found to bind to the 3’-untranslated region (UTR) of the lactate dehydrogenase (LDHA), which consequently reduced the expression of both mRNA and protein of LDHA. Interestingly, overexpression of miR-204-3p decreased glucose consumption and lactate production of bladder cancer cells. Overexpression of LDHA relieved the growth inhibition and cell apoptosis enhancement by miR-204-3p in bladder cancer cells. These results demonstrated that miR-204-3p negatively modulated the proliferation of bladder cancer cells via targeting LDHA-mediated glycolysis. MiR-204-3p might be a promising candidate for designing anti-cancer medication.